Lifelong guidance across Europe : reviewing policy progress and future prospects - (:unkn) unknown (Publications Office of the European Union, 2011)
"This Cedefop report reviews progress made across Europe in 2007-10 in developing guidance policy coordination, quality assurance mechanisms, access to services and career management skills. The review shows that the EU policy framework and changing economic conditions have encouraged closer collaboration between policy makers, guidance professionals and researchers. Together they are locating assets and resources, identifying and engaging stakeholders, defining and completing joint goals and objectives, and balancing a diverse range of interests. These partnerships help everyone involved - education and employment sectors, various policy levels, and practitioners - to work more efficiently. The challenge is now to agree on what needs to be done to create a truly lifelong guidance system across all sectors, life situations and countries. Such services will support not just lifelong learning, but social inclusion and active citizenship for all." The review covers the EU-27, Norway and the four EU candidate countries Croatia, the former Yugoslav Republic of Macedonia, Iceland and Turkey. (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; L 5 Beratung & Orientierung; I 2.2 Europa; I 2.2.2 Osteuropa; I 2.2.1 Westeuropa; EU-Bildungspolitik; Lebenslanges Lernen; Bildungsberatung; Laufbahnberatung; Qualitätssicherung; Netzwerk; Europäische Union; Kroatien; Mazedonien; Island; Türkei